Analysis of Factors Affecting The Interest of Using Financial Technology (Fintech) - Abid Muhtarom; Inka Alda Putri Wahyulicha; Evi Fitrotun Najiah; Ruswaji Ruswaji; Lilik Nurkholidah; Uzlifatul Masruroh Isnawati; Luluk Nur Azizah (Jurnal Ekonomi, 2020)
- Research has been conducted on the perception of usability, the perception of the speech, the perception of comfort, risk and confidence in the interest in using financial technology in the economics Faculty of Islamic University of Lamongan. This research aims to know the perception of usability, perception of the speech, perception of comfort, risk and confidence in the interest of using financial technology in economics Faculty of Islamic University of Lamongan. This study used quantitative approach using Survey research type. The sampling technique used is purposive sampling, the population in this research is the economics faculty student of the Islamic University of Lamongan school year 2019-2020, So that the selected sample as much as 95 students were counted from the Slovin formula. The analysis is done by spreading a poll or questionnaire online then conducted partial and simultaneous tests using independent sample T-Test with significant value 0,05. A partial test has been performed and produced tCount Greater than the ttable (X1 = 1,466<1,66216. X2 = 0,819>1,66216. X3 = 1,150<1,66216, X4 = -0,556<1,66216, X5 = 3,446<1,66216). So it can be known that the perception of usability, perception of benefits, perception of comfort, and risk does not have the influence of inopportune interest in using financial technology while the trust variable has partial influence on interest Using financial technology. And simultaneous testing has been conducted, produced FCount Greater than the Ftable (10,853>2,32). So it can be known that the perception of usability, the perception of ease, perception of comfort, risk and trust have a simultaneous influence on interest in using financial technology.